Male acoustic display in the sand goby – Essential cue in female choice, but unaffected by supplemental feeding - Blom, Eva-Lotta (2022)
Many teleost fishes use acoustic and visual signalling during courtship. Such displays may convey information about body condition. Here we experimentally altered body condition of sand goby (Pomatoschistus minutus) males to examine effects on acoustic and visual courtship and subsequent spawning decisions. Over two weeks, males fed in excess were fed daily, whereas food-deprived males were fed once a week. Females only spawned with males that produced courtship sound. However, there were no treatment effects on the occurrence of spawning and males fed in excess did not invest more in visual or acoustic courtship than food-deprived males. That said, males fed in excess built more well-covered nests, with more sand piled on top, compared to fooddeprived males. Male condition measured as lipid content differed significantly between treatments. However, only males fed in excess differed in lipid content from wild caught males, indicating that in nature, males are of similar condition to males in the low condition treatment group. Apart from the importance of courtship sound, the only male or female behaviour predicting reproductive success was if male displayed in the nest opening. Males often produce courtship sounds together with a visual display in this position. A female dark-eye display did not associate with reproductive success which, together with previous results, suggest a non-ornamental function of this trait. We conclude that male courtship sounds appear to be crucial in female mate choice, but the information content of the courtship sounds and how it relates to male condition remains elusive.